Two new lichenicolous Arthonia species from Scandinavia - Westberg, Martin; Isaksson, Robin; Frisch, Andreas (Phytotaxa, 2025)
Arthonia epiramboldia and A. scrobiculatae are described new to science and reported from localities in northern Norway and Sweden. Arthonia epiramboldia grows on the crustose lichen Ramboldia cinnabarina, whereas A. scrobiculatae grows in the soralia of the foliose Lobaria scrobiculata. Both species were found to be affiliated to the Bryostigma clade by RAxML and Bayesian analysis of concatenated mtSSU, nrLSU, RPB2, and nrITS sequence data. Arthonia circinata, lichenicolous on Umbilicaria spp., and the recently described A. subclemens and A. epipolytropa, both lichenicolous on Lecanora polytropa s. lat., are confirmed to belong to the Bryostigma clade. In addition, A. toensbergii is reported for the first time from Sweden.